2017
DOI: 10.1002/pro.3139
|View full text |Cite
|
Sign up to set email alerts
|

Selective cysteine modification of metal‐free human metallothionein 1a and its isolated domain fragments: Solution structural properties revealed via ESI‐MS

Abstract: Human metallothionein 1a, a protein with two cysteine-rich metal-binding domains (α with 11 Cys and β with 9), was analyzed in its metal-free form by selective, covalent Cys modification coupled with ESI-MS. The modification profiles of the isolated β- and α-fragments reacted with p-benzoquinone (Bq), N-ethylmalemide (NEM) and iodoacetamide (IAM) were compared with the full length protein using ESI-mass spectral data to follow the reaction pathway. Under denaturing conditions at low pH, the reaction profile wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 60 publications
2
28
1
Order By: Relevance
“…This indicates that oxidative dimer formation is not likely, even in the apo‐protein with many redox active Cys residues, as long as precautions are taken to limit oxygen exposure. This fits with structural models of apo‐MTs that have proposed the Cys residues to be buried within the protein as a globular structure, similar to the holoprotein …”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…This indicates that oxidative dimer formation is not likely, even in the apo‐protein with many redox active Cys residues, as long as precautions are taken to limit oxygen exposure. This fits with structural models of apo‐MTs that have proposed the Cys residues to be buried within the protein as a globular structure, similar to the holoprotein …”
Section: Resultssupporting
confidence: 86%
“…In the unfolded metal‐free state, the charge‐state distribution shifts to a slightly higher range, as can be seen in this and other works. When all Cys residues in MT are covalently modified by N ‐ethylmalemide, adding 2500 Da to the mass of the protein, the average charge‐state shift is increased by less than 2 . A report by our group showed a large shift in the charge states of the apo‐protein upon acidification to pH 1.8, in contrast to most other studies which show only a slight shift in charge states .…”
Section: Introductioncontrasting
confidence: 64%
“…That the apo-protein adopts a secondary structure is supported by experiments showing that the reactivity of cysteinyl sulfhydryl groups differs in native and denatured apo-MT, and that the rate of binding of Cd 2+ to the protein also varies between these two states [95,96]. …”
Section: Metal-unsaturated Metallothionein and The Trafficking Of mentioning
confidence: 99%
“…That the relative abundance can be extracted with confidence from the ESI-MS experiment indicates that the structural changes upon metalation do not result in radically different ionization efficiencies between species. Conclusion from these many reported methods, including techniques such as charge state analysis [ 19 ], ion-mobility (IM) MS [ 20 ], and residue modification coupled with ESI-MS [ 21 ], and LC-MS [ 22 ], cast doubt on the model of a completely unstructured apo-MT at physiological pH. However, these mass spectral studies were not the first to suggest a compact and globular structure, as theoretical calculations predicted that the cysteine residues in the apo-MTs were buried and not freely accessible to the solvent [ 23 ] and FRET studies [ 24 , 25 ] of recombinant MTs in the early 2000s showed that there was also negligible volume change in the protein upon metalation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our group and others have demonstrated that the reaction with cysteine alkylation agents, such as n -ethylmaleimide (NEM), p -benzoquinone, and iodoacetamide can be used to determine the folded state of apo-MT under various conditions [ 21 ]. The most common denaturants used in biochemical unfolding studies are acidity and guanidinium chloride (GdmCl).…”
Section: Introductionmentioning
confidence: 99%